Macchine Guerriere Autonome - Ceola, Paolo (Filosofia, 2020)
Artificial Intelligence is an epochal revolution, a real evolutionary leap in humanity, in both the cognitive sphere and that of material and social consequences. In the military, its enormous impact is looming: the Lethal Autonomous Weapons Systems introduce changes in the art of war to make the advent of firearms pale between the fifteenth and sixteenth centuries, and in this sense they can be equated only to nuclear weapons. The essay aims to examine the issues and problems inherent in the advent of autonomous weapons, not even remotely piloted by humans, in both the tactical and strategic spheres. We also try to consider the problem from the point of view of both classical war theory and international law. The positive effects of this technological revolution are discussed in the course of the text and do not constitute a separate chapter.